Peran Kepemimpinan Kepala Sekolah Dalam Membentuk Karakter Religius Peserta Didik Di SMK Cendekia Madiun - Ahmad Mushthofa; Muqowin Muqowin; Aqimi Dinana (Kelola: Jurnal Manajemen Pendidikan, 2022)
The research that the researchers conducted had the aim of knowing and describing the role of a principal's leadership in shaping religious character and to find out how the implementation of the principal's role in shaping the religious character of students at SMK Cendekia Kota. Madison. The research uses descriptive (qualitative) research and uses a technique or method of purposive sampling. There are six roles of a principal in shaping the religious character of students. From the research, the researcher shows that the principal of SMK Cendekia Madiun carries out the role as a leader by carrying out the principal's leadership function; as an educator by providing knowledge or teaching, encouragement and direction to teachers, employees and students; as a manager by planning activities to realize religious character building activities; as administrator with the preparation, financing and documentation of all school programs. The school principal provides support for religious activity programs, starting from the provision of funds in the form of fees; as a leader by formulating and determining the goals to be achieved and deciding the planning of religious character building activities; being a motivator providing a motivation to all teachers, employees, students and managing the physical environment and work atmosphere; as a supervisor by carrying out various observations, supervision and control, in the implementation of religious character building activities.